Pengaruh Motivasi Kerja dan Komitmen Organisasi terhadap Kepuasan Kerja Pegawai dengan OCB Sebagai Variabel Intervening (Studi Kasus pada IGD RSUD Tgk. Chik Ditiro Sigli) - Saifuddin, Saifuddin; Yusuf, M.; Danil, Mahyu (Aceh Cooperative Care, 2025)
The research examines the influence of work motivation and organizational commitment on employee job satisfaction. Also seen from the organizational citizenship behavior (OCB) factor of employees. The research was conducted at the Emergency Room (IGD) of Tgk. Chik Ditiro Sigli Hospital. The research method used an associative method with a quantitative approach, using path analysis. The sample in this study was 85 employees. The results of the study showed that 1) There is a direct and indirect influence of work motivation on job satisfaction, through the organizational commitment variable, which is 41%. 2) There is a direct and indirect influence of organizational commitment on job satisfaction, through the work motivation variable, which is 37.93%. 3) There is a relationship between work motivation and organizational commitment of 0.498. 4) There is a direct and indirect influence of work motivation on OCB, through the organizational commitment variable, which is 23.55%. 5) There is a direct and indirect influence of organizational commitment on organizational citizenship behavior (OCB), through the work motivation variable, which is 25.67%. 6) Simultaneously, work motivation and organizational commitment influence employee OCB. 7) The magnitude of the total influence of work motivation and organizational commitment on employee OCB, through the job satisfaction variable, is 15.98%.